Transdisciplinarity immersed in fairy tales: The search for innovative early childhood education (Research, Society and Development, 2023)
This article is an excerpt from the dissertation linked to the Professional Master's Course in Public Policies and Educational Management, at the Federal University of Santa Maria (UFSM/RS), from the Pedagogical Management and Educational Contexts Research Line (LP/2); As the objective of this article, we wish to share innovative practices in classroom management: interdisciplinarity and transdisciplinarity, specifically on transdisciplinary pedagogical practice in Early Childhood Education, through fairy tales. As a question of concern, which we seek to answer: Is it possible, through interdisciplinarity and transdisciplinarity, to integrate different areas of knowledge and build innovative learning, thus developing an entire education, based on Gaucho fairy tales? The methodology used was qualitative research, carried out through (auto)biographical narratives, related to pedagogical practices developed with a Preschool B class, with 19 students aged five and six, from an EMEI in Santa Maria/RS. From these experiences, storytelling in Early Childhood Education was given a new meaning, innovating interdisciplinary and transdisciplinary pedagogical practices, in the search for the formation of the entire Human Being, through activities that awakened children's creativity, lightness and enchantment, being a rewarding experience for the students and for me, as an educator.